2022
DOI: 10.15359/ru.36-1.34
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de la atención visual de estudiantes a través de gafas espía

Abstract: La atención visual es un indicador importante en las interacciones entre docentes y estudiantes. Este artículo presenta los resultados de un estudio que buscó determinar cómo fluctúa la atención visual que los estudiantes prestan a la persona docente durante sus clases de matemáticas e inglés y detectar posibles diferencias en dicha atención. El estudio se llevó a cabo en una escuela secundaria con una muestra de 16 estudiantes (varones). Los datos se obtuvieron a través de una mini cámara de video, montada so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Touch can be a mediatory tool for boosting students’ engagement in educational activities. Touch, if used properly, can enhance not only social relations but also “learning and teaching connections” ( Rosa et al, 2020 ; Rosa and Farsani, 2021 ; Farsani and Villa-Ochoa, 2022 ); that is, it can strengthen students’ involvement in educational activities and create a context in which students are actively engaged in learning activities. Furthermore, we would like to stress and highlight that teachers’ touch appears to be a resource that can empower teachers and educators to better engage with their students.…”
Section: Discussionmentioning
confidence: 99%
“…Touch can be a mediatory tool for boosting students’ engagement in educational activities. Touch, if used properly, can enhance not only social relations but also “learning and teaching connections” ( Rosa et al, 2020 ; Rosa and Farsani, 2021 ; Farsani and Villa-Ochoa, 2022 ); that is, it can strengthen students’ involvement in educational activities and create a context in which students are actively engaged in learning activities. Furthermore, we would like to stress and highlight that teachers’ touch appears to be a resource that can empower teachers and educators to better engage with their students.…”
Section: Discussionmentioning
confidence: 99%
“…This means that not only daily concepts but also scientific concepts can have motor strength, and this motor strength is realized in gestures that are used to talk about them. Results of many studies have demonstrated that gestures enhance the process of teaching and learning sciences (e.g., Alibali and Nathan, 2012 ; Alibali et al, 2014 ; Martinez-Lincoln et al, 2018 ; Rosa and Farsani, 2021 ; Farsani and Villa-Ochoa, 2022 ; Khatin-Zadeh et al, 2023a ). Many of these concepts such as those discussed in mathematics (numbers, limit of function, continuity, etc.)…”
Section: Sensory and Action Effector Strengths Of Conceptsmentioning
confidence: 99%
“…Since mathematical subjects are often discussed in terms of abstract symbols in mathematics textbooks, many learners are faced with difficulties to digest these generalities. Luckily, embodied mathematics teaching and learning has offered a solution to this problem (e.g., Radford, 2009 ; Sinclair and Heyd-Metzuyanim, 2014 ; Dackermann et al, 2017 ; Nemirovsky et al, 2020 ; Rosa et al, 2020 ; Rosa and Farsani, 2021 ; Farsani and Villa-Ochoa, 2022 ). At least, it can be said that this approach has a lot of potentials to overcome the difficulties that learners are faced with when trying to learn mathematics.…”
Section: Introductionmentioning
confidence: 99%